The Effect of Green Brand Knowledge and Green Brand Positioning on Purchase Intention Mediated by Attitude Towards Green Brand: Study on Stainless Steel Straw Products by Zero Waste - Pebrianti, Wenny; Aulia, Mujahida (JDM (Jurnal Dinamika Manajemen), 2021)
This study aims to analyze the effect of green brand knowledge and green brand positioning on pur chase intention mediated by attitude towards the green brand on stainless steel straw products in Pon tianak City. The population in this study was Pontianak City people who knew about stainless stee straw products. The samples in this study were 100 respondents employing the purposive sampling technique. The data analysis model used in this study was the Structural Equation Model-Partial Least Square (SEM-PLS). Based on the hypothesis submission, it was concluded that green brand knowledge and green brand positioning significantly affected the attitude towards the green brand. The result of further hypothesis testing showed that green brand knowledge and attitude towards green brands had a significant effect on purchase intention, while green brand positioning did not significantly affect purchase intention. The mediation effect test revealed that attitude towards green brand mediated the relationship between green brand positioning and purchase intention, but the attitude towards green brand could not mediate the relationship between green brand knowledge and purchase intention..